(untitled) - Gilbert, Rita (Boston, 2005)
This book is a basic art text for college student and other interested readers. Its offers a broad introduction to the nature, vocabulary, media, and history of visual art, illustrated by hundreds of examples draw from many cultures and across many centuries
Keywords: Art appreciation,Đánh giá nghệ thuật